The revolt of the Black athlete - Edwards, Harry 1942- (University of Illinois Press, 2018)
"In 1968, Harry Edwards, virtually alone, opposed the U.S. Olympic Committee, the political establishment, and the mass media and made an international issue of the Olympic boycott movement. In this book, he explains why he organized the Olympic boycott, why black athletes revolted, and why they are prepared to do so again. Exposing the inherent political nature of sports, Edwards illustrates how blacks can use athletics to their advantage and relates the revolt of the black athlete to the larger spirit of revolt of black citizens during the Civil Rights movement. In the process, Edwards explodes the myth that black athletes on scholarship receive an education or fair treatment in return for their efforts. Beyond college sports, Edwards found the degradation of the black athlete extends into the world of professional sports. He comments on the lack of black owners, managers, and head coaches, league pay scales, the press vendetta against Muhammad Ali, and the quarantining of John Wooten of the Cleveland Browns. Other topics discussed include the background and workings of the Olympic Committee for Human Rights, the boycott of the New York Athletic Club Track Meet, and the actions taken by Lew Alcindor, Tommie Smith, John Carlos, and other black athletes in the struggle for justice and dignity. Originally published in 1969, the 50th Anniversary edition puts "The Revolt of the Black Athlete" in context for today's readers. With 2015's University of Missouri football teams boycott and the need for movements like Black Lives Matter, Edward's critique still rings true 50 years later"...
"With a New Introduction and Afterword"...T.p. - Includes bibliographical references and index
Keywords: Geschichte; SOCIAL SCIENCE / Ethnic Studies / African American Studies / bisacsh; SPORTS & RECREATION / History / bisacsh; HISTORY / United States / 20th Century / bisacsh; African American athletes -- History -- 20th century; African American athletes -- Political activity -- History -- 20th century; African American athletes -- Social conditions; Sports -- Social aspects -- United States -- History -- 20th century; Sports -- Political aspects -- United States -- History -- 20th century; Sports -- United States -- History -- 20th century; Discrimination in sports -- United States -- History -- 20th century; SOCIAL SCIENCE / Ethnic Studies / African American Studies; SPORTS & RECREATION / History; HISTORY / United States / 20th Century; Schwarze; Sport; USA